2010
DOI: 10.1148/radiol.2541090953
|View full text |Cite
|
Sign up to set email alerts
|

Reasons Women at Elevated Risk of Breast Cancer Refuse Breast MR Imaging Screening: ACRIN 6666

Abstract: Purpose:To determine reasons for nonparticipation in a trial of supplemental screening with magnetic resonance (MR) imaging after mammography and ultrasonography (US). Materials and Methods:Women ( n = 2809) at elevated risk of breast cancer were enrolled in the American College of Radiology Imaging Network 6666 US Screening Protocol at 21 institutions. Fourteen institutions met technical and experience requirements for this institutional review board-approved, HIPAA-compliant substudy of supplemental screenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
96
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(100 citation statements)
references
References 34 publications
4
96
0
Order By: Relevance
“…11 However, there are substantial concerns about high costs and limited access to high-quality MRI services. Furthermore, breast MRI is time-consuming, problematic for claustrophobic 12 or very obese patients, and prohibited for women with pacemakers. Thus, neither mammography nor MRI is ideally suited for evaluating and monitoring breast density.…”
Section: Introductionmentioning
confidence: 99%
“…11 However, there are substantial concerns about high costs and limited access to high-quality MRI services. Furthermore, breast MRI is time-consuming, problematic for claustrophobic 12 or very obese patients, and prohibited for women with pacemakers. Thus, neither mammography nor MRI is ideally suited for evaluating and monitoring breast density.…”
Section: Introductionmentioning
confidence: 99%
“…In one study, Berg and colleagues examined the reasons why women with high risk for breast cancer refused breast MRI. Their results showed that even 10.6% (133 of 1215) patients, in whom breast MRI was indicated, were not examined due to claustrophobia [24] and that claustrophobia was the most common reason for unperformed MRI (25.4%).…”
Section: Discussionmentioning
confidence: 99%
“…However, this recommendation can lead to more false-positive findings, and thereafter to further worsening in the specificity of MRI after excisional biopsy [76]. It should be noted that women at high breast cancer risk often turn down invitations to participate in MRI surveillance programs due to fear of being sent for biopsy or other testing [77]. There is a pressing need to improve breast cancer imaging strategies to be better adapted to women's needs, especially their risk profile [78].…”
Section: Detection Of Pc For Surveillance Of Women At High Breast Canmentioning
confidence: 99%